Primary structure and expression of a pathogen-induced protease (PR-P69) in tomato plants: Similarity of functional domains to subtilisin-like endoproteases. - Tornero, P (1996)
A 69-kDa proteinase (P69), a member of the pathogenesis-related proteins, is induced and accumulates in tomato (Lycopersicon esculentum) plants as a consequence of pathogen attack. We have used the polymerase chain reaction to identify and clone a cDNA from tomato plants that represent the pathogenesis-related P69 proteinase. The nucleotide sequence analysis revealed that P69 is synthesized in a preproenzyme form, a 745-amino acid polypeptide with a 22-amino acid signal peptide, a 92-amino acid propolypeptide, and a 631-amino acid mature polypeptide. Within the mature region the most salient feature was the presence of domains homologous to the subtilisin serine protease family. The amino acid sequences surrounding Asp-146, His-203, and Ser-532 of P69 are closely related to the catalytic sites (catalytic triad) of the subtilisin-like proteases. Northern blot analysis revealed that the 2.4-kb P69 mRNA accumulates abundantly in leaves and stem tissues from viroid-infected plants, whereas the mRNA levels in tissues from healthy plants were undetectable. Our results indicate that P69, a secreted calcium-activated endopeptidase, is a plant pathogenesis-related subtilisin-like proteinase that may collaborate with other defensive proteins in a general mechanism of active defense against attacking pathogens.